Cognitive and pragmatic potential of auditory perceptions in the poetics of Vasyl Stus (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
The article investigates the necessety and prospects of scientific studies in the field of sensory or perceptual linguistics. It focuses on the so-called perceptual vocabulary, which illustrates the feelings that are localized in the mind through the senses such as: vision, hearing, olfacting, taste, touch. They are the corresponding “communication channels” of a person with the world. Perceptual vocabulary is considered as the important element of the artistic, in particular the poetic, model of the world. It reflects author individual ideas and images as well as represents value orientations. Moreover it actualises meanings, based on the author’s worldview, his sensory experience. It also reveals new associative connections, which, respectively, predetermines a high degree of emotional influence on the addressee. This paper deals with the cognitive and pragmatic potential of auditory perceptives as structural elements of Vasyl Stus poetics. It is emphasized that the audition situations, created by the writer, actualize the samples, which are not only the representatives of the external world, but also the representatives of the internal state of the author’s lyrical character. This article demonstrates the semantic load of auditory sensory images in poetic speech. It reveals nuclear lexemes (first of all verbs and verbal nouns) that illustrate and reveal cognitive images of audition situations. The paper highlights the situations in which the perceptual lexem to shout and its derivatives verbalize the extremely unpleasant and painful feelings of the lyrical character, his emotional discomfort, unbearable mental sorrows. Moreover, the structural elements of the cognitive image in the audition situations are revealed. Subjects / objects of auditory perception from the standpoint of collective experience and the author’s worldview are presented.
Keywords: auditory perceptive; perceptual vocabulary; perceptual modus; cognitive image of audition situation; poetic speech